2009
DOI: 10.1021/jo8023818
|View full text |Cite
|
Sign up to set email alerts
|

Facile Stereoselective Synthesis of Fluorinated Flavanone Derivatives via a One-Pot Tandem Reaction

Abstract: A series of fluorinated flavanones were synthesized in moderate to good yields with excellent diastereoselectivities under mild reaction conditions via a one-pot tandem procedure involving a proline-catalyzed Knoevenagel condensation, a Michael addition, and an electrophilic fluorination by NFSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…57 Combining the regioselective hydroformylation and a decarboxylative Knoevenagel reaction allowed for the development of an efficient, one-pot procedure for the synthesis of (E)-a,b-unsaturated carboxylic acid (47) The reaction of 2-(N-alkenyl-N-aryl)amino-4-oxo-4H-1-benzopyran-3-carbaldehyde (50) with dimedone by heating in ethanol in the presence of catalytic amount of pyridine produces cyclic heterocycles (51) bearing both pyridine and pyran rings via the Knoevenagel-hetero Diels-Alder domino sequence reaction (Scheme 18). 60 The Knoevenagel condensation of cyclic ketones (52) with benzylonitrile (53) and N,N 0 -dimethylbarbituric acid (54) afforded heterodynes (2-cycloalkylidene-3-oxo-3-phenyl-propionitriles 55 and 5-cycloalkylidene-1,3-dimethylpyrimidine-2,4,6-triones 56), which underwent hetero-Diels-Alder cycloaddition reaction with enol ethers (57 and 58) giving sterically hindered dispiropyrans (59, 60) (Scheme 19 and Table 3).…”
Section: One-pot Sequential Reactionsmentioning
confidence: 99%
“…57 Combining the regioselective hydroformylation and a decarboxylative Knoevenagel reaction allowed for the development of an efficient, one-pot procedure for the synthesis of (E)-a,b-unsaturated carboxylic acid (47) The reaction of 2-(N-alkenyl-N-aryl)amino-4-oxo-4H-1-benzopyran-3-carbaldehyde (50) with dimedone by heating in ethanol in the presence of catalytic amount of pyridine produces cyclic heterocycles (51) bearing both pyridine and pyran rings via the Knoevenagel-hetero Diels-Alder domino sequence reaction (Scheme 18). 60 The Knoevenagel condensation of cyclic ketones (52) with benzylonitrile (53) and N,N 0 -dimethylbarbituric acid (54) afforded heterodynes (2-cycloalkylidene-3-oxo-3-phenyl-propionitriles 55 and 5-cycloalkylidene-1,3-dimethylpyrimidine-2,4,6-triones 56), which underwent hetero-Diels-Alder cycloaddition reaction with enol ethers (57 and 58) giving sterically hindered dispiropyrans (59, 60) (Scheme 19 and Table 3).…”
Section: One-pot Sequential Reactionsmentioning
confidence: 99%
“…[63] They were able to access a variety of 3-fluorocarboxyflavanones and chromanones 62 , which included activated and deactivated substitution patterns at R. It is important to note that chromanones generally gave lower selectivities than flavanones and that the 2-furanyl substrate represented the most weakly performing of the aromatic substrates, with a yield of 56% and a selectivity of 73% ee .…”
Section: Carbon–heteroatom Bond Formationmentioning
confidence: 99%
“…Zhao and co-workers followed their earlier tandem work [63a] with a recent report on the tandem intramolecular cyclization/functionalization of alkylidenes 63 (Scheme 30). [57] They found that modified cinchona alkaloids were suitable catalysts for the reactions and provided products in good yields and with high enantioselectivities.…”
Section: Carbon–heteroatom Bond Formationmentioning
confidence: 99%
“…[8,9] Our group has developed a onepot tandem reaction for the synthesis of fluorinated flavanones, from b-ketoesters and aldehydes, with excellent diastereoselectivities. [10] On the basis of these results, we envisaged that by using an appropriate bifunctional catalyst, an organocatalytic, asymmetric, intramolecular oxa-Michael addition of 1 would produce enantioenriched 2, which could then be subjected to electrophilic fluorination to provide novel, chiral, fluorinated flavanone derivatives (Scheme 1). Herein, we report the details of this research.…”
mentioning
confidence: 99%
“…[13] To propose a mechanism for the reaction, we assumed that the oxa-Michael addition was the enantiodiscriminating step and the stereocenter thus formed would govern the stereoselectivity of the electrophilic fluorination process as we have previously demonstrated. [10] Based on the experimental results and previous studies, [11] we proposed a transitionstate model to explain the stereochemical outcome of the reaction (Scheme 3). The bifunctional catalyst may activate both the nucleophile and the electrophilic acceptor through a hydrogen-bonding interaction, directing the oxygen nucleophile to attack the Re face of the double bond to form the Rconfigured product.…”
mentioning
confidence: 99%